Evaluation of micro-biodiversity in three Spratly islands by metagenomics - Cuong, Pham Kien; Nga, Tran Thi Huyen; Thu, Nguyen Thi Tam; Ha, Bui Thi Thu; Hoai, Nguyen Thu; Cong, Le Thi Nhi; Linh, Nguyen Viet (Vietnam Journal of Science and Technology, 2026)
The biodiversity of micro community of the soil in three islands of Spratly Island, Vietnam has been analyzed by metagenomic. A total of 77,689 reads were obtained from the sample of Spratly Island (Truong Sa Lon - TSL), in the meanwhile there are only 62,447 reads from the sample of Sand Cay Island (Son Ca - SC) and 70,150 reads from that of Southwest Cay Island (Song Tu Tay - STT). The validated reads of islands are 35,253, 10,279, and 10,380, respectively. The reads from TSL were divided into 31 phyla, 80 classes, 185 orders, 291 families, 458 genera and 397 species. Those from SC included 24 phyla, 45 classes, 98 orders, 133 families, 176 genera and 100 species. STT has 20 phyla, 39 classes, 95 orders, 129 families, 169 genera and 110 species. Although the component and proportion of each taxonomic level is unique and different from each other and from those collected in other island research, the results have shown the diversity and characteristics of micro-biomes of TSL, SC and STT islands. These characteristics reflect the natural and human conditions affecting and determine the dominance of bacteria population of each island.